Growth Arrest-Specific 6 and Cardiometabolic Risk Factors in Patients with Psoriasis - SEÇKİN GENÇOSMANOĞLU, DİLEK; SÜNBÜL, MURAT; ÖZGEN, ZÜLEYHA (WILEY, 2015)
ObjectivesAn increased risk for cardiovascular disease with psoriasis has been reported. Growth Arrest-Specific 6 (GAS6) amplifies pro-inflammatory endothelial cell activation via TAM receptors. However, it also inhibits inflammation by multiple mechanisms including phagocytosis. The objective of this study was to investigate whether plasma GAS6 levels are associated with conventional cardiometabolic (CM) risk factors in patients with psoriasis. MethodsForty patients diagnosed with psoriasis (22 male, mean age: 43.313.8years) and 40 age-/sex-matched healthy controls (22 male, mean age: 39.38.9years) were included in the study. CM risk factors (hypertension, hyperlipidemia, diabetes mellitus, and cigarette smoking) were identified. GAS6 levels were measured by ELISA. ResultsThere were no significant differences between the plasma GAS6 levels of patients with psoriasis compared to the control group (6.6 +/- 2.0ng/mL, 7.6 +/- 2.8ng/mL, respectively, P>0.05). However, GAS6 levels of patients with psoriasis having a smoking history (n=11) were significantly lower than both patients with psoriasis who had no smoking history (n=29) and controls (5.5 +/- 1.7ng/mL, 6.9 +/- 1.9ng/mL, 7.6 +/- 2.8ng/mL, respectively, P<0.05). Similarly, psoriasis patients with at least one CM risk factor showed lower GAS6 levels compared to subjects without any CM risk factor (5.7 +/- 1.7ng/mL, 7.3 +/- 2.0ng/mL, P<0.01). There was no correlation between the GAS6 level, disease duration or PASI score (r=0.150, -0.150, and P=0.310, 0.398, respectively). ConclusionsThis pilot study provides the first evidence in humans for an association between low plasma GAS6 levels and conventional risk factors in psoriasis. Further large scale, prospective studies are needed to confirm these results.
Keywords: Atherosclerosis; Growth Arrest-Specific 6; Psoriasis; Risk Factors; SYSTEMIC-LUPUS-ERYTHEMATOSUS; K-DEPENDENT PROTEINS; SMOOTH-MUSCLE-CELLS; TAM RECEPTORS; CARDIOVASCULAR RISK; DISEASE-ACTIVITY; VASCULAR CALCIFICATION; PLASMA-CONCENTRATIONS; ARTERIAL STIFFNESS; ENDOTHELIAL-CELLS